Reflections on Separate Enterprise vs. Formulary Apportionment - van Weeghel, Stef (Challenges of Contemporary Tax Law: Jubilee Book Dedicated to Professor Włodzimierz Nykiel. Volume II, 2024)
This contribution contains reflections on the international system for the taxation of business profits and puts the current discussion regarding the OECD Pillar One project in a historic context. The OECD transfer pricing guidelines imply that global formulary apportionment is to be rejected, but the Pillar One project in fact would introduce that system as an overlay to the existing separate enterprise method.